A Family of Integer-Point Ternary Parametric Subdivision Schemes. (14th October 2021) - Mustafa, Ghulam; Asghar, Muhammad; Ali, Shafqat; Afzal, Ayesha; Liu, Jia-Bao
Abstract : New subdivision schemes are always required for the generation of smooth curves and surfaces. The purpose of this paper is to present a general formula for family of parametric ternary subdivision schemes based on the Laurent polynomial method. The different complexity subdivision schemes are obtained by substituting the different values of the parameter. The important properties of the proposed family of subdivision schemes are also presented. The continuity of the proposed family is C 2 m . Comparison shows that the proposed family of subdivision schemes has higher degree of polynomial generation, degree of polynomial reproduction, and continuity compared with the exiting subdivision schemes. Maple software is used for mathematical calculations and plotting of graphs.